Emerging roles of selenium on metabolism and type 2 diabetes - Zhao, Jiuxiang; Zou, Hong; Huo, Yanling; Wei, Xiaoyi; Li, Yu (Frontiers in Nutrition, 2022)
Selenium is recognized as an essential element for human health and enters human body mainly via diet. Selenium is key constituent in selenoproteins, which exert essential biological functions, including anti-inflammatory and antioxidant effects. As type 2 diabetes, insulin resistance, β-cell dysfunction, and impaired glucose tolerance are all reported to associate with oxidative stress, selenium is expected to protect against type 2 diabetes based on the antioxidant and anti-inflammatory properties of several selenoproteins. The mechanism between selenium and type 2 diabetes remains complex, despite of the clear link between certain selenoproteins with glucose metabolism or insulin resistance. According to research, several selenoproteins participate in type 2 diabetes regulation, including glutathione peroxidase, selenoprotien P and selenoprotein S. To better understand the relationship between selenoproteins and type 2 diabetes, we summarize the existing mechanism of action. Understanding the association between selenium and type 2 diabetes is important for guiding clinical practice, developing effective public health policies, and ultimately counteracting health issues associated with selenium deficiency.